Dispersive analysis of τ− → π−π⁰ντ Belle data - Gómez Dumm, Daniel Alberto (2014)
We analyse Belle data on the decay τ− → π−π⁰ντ using a dispersive representation of the vector form factor which is consistent with chiral symmetry and preserves analyticity and unitarity exactly. We fit the unknown theoretical parameters from the data, determining the values of the related low-energy observables 〈 r² 〉πV and cπV. The implementation of isospin breaking effects is also discussed.